Genetic assessment of 23 cassava, Manihot esculenta Crantz, genotypes at two agroclimatic zones in Nigeria - Oduwaye, O.A.; Ojo, D.K.; Mkumbira, J.; Alake, C.O.; Adenuga, O.; Mapayi, E.F. (Plant Breeding and Seed Science, 2012)
This study investigated genetic diversity among 23 cassava genotypes in two-agro-ecological zones (Ibadan and Mokwa), Nigeria. The experiment was conducted using a randomized complete block design with three replicates. The cassava genotypes were evaluated for tuber yield, fresh weight of tuber, number of tu- bers, tuber girth and length, dry matter and chlorophyll concentration. The data collected were subjected to analysis of variance and differences among the genotypes were computed using Duncan’s multiple range test. Single linkage cluster and FASTCLUS analysis were used to group the cassava genotypes. Genotypic and phenotypic coefficient of variability, heritability and genetic advance were also evaluated. Genotype, environ- ment and genotype × environment interaction (GEI) were significant (P < 0.01) for most of the traits evalu- ated. The magnitude of the environment was higher compared to genotype and GEI. Comparative mean per- formance varied from location to location. Tuber yield ranged from 0.32 for 92/0325 to 0.90 kg for 99/3073 with mean of 0.58 kg, and 0.16 kg for 82/00058 to 0.67 kg for 98/0581 with mean of 0.35 kg in Mokwa. Higher genotypic and phenotypic coefficients of variability were observed in Ibadan than Mokwa, for most of the characters. The interrelationships among the characters revealed the superiority of some cassava genotypes for a character in one location and not in the other location. However, breeding potentials exists among the cassava genotypes across the two environments.